Type of endorser and media modality in halal cosmetic advertising on Instagram - Fitriah Dwi Susilowati; Sri Abidah Suryaningsih; Khusnul Fikriyah; Wulan Santikawati Ulfa (Al-Kharaj: Journal of Islamic Economic and Business, 2022)
The purpose of this study is to investigate the difference in consumer attitude toward brand and advertising, and purchase intention when consumers encounter halal cosmetic advertising on Instagram using different types of endorsers and presentation modalities. The halal industry is increasingly experiencing rapid development, including in the halal cosmetic industry. Halal cosmetics is starting to be liked by young people. To reach the young segment of the market, halal cosmetics use social media such as Instagram to do marketing. An experiment design was conducted involving 132 undergraduate students. The data analysis method used was MANOVA. The results of this study indicate that the use of influencers is more effective in generating positive consumer attitudes compared to celebrity endorsers. Halal cosmetic marketers who advertise on Instagram want to make consumers pay more attention to the advertisements posted by these marketers and not scroll to other feeds, it is suggested that they use influencer endorsers and rich modality strategies in their advertisements. This research has novelty in providing an overview of marketing halal products on social media, especially on Instagram